Cutaneous Manifestations of Chikungunya Fever: An outbreak in North India - Dimple Chopra; Goel S; Bansal S; Arora N; Singla A (GMC Patiala Journal of Research and Medical Education, 2018)
Chikungunya(CKG) is acute viral arboviral disease transmitted by the bite of aedes ageypti and aedes albopictus mosquito. Recently, CKG is emerged in north india affecting large population. CKG is characterized by high grade fever, retro-orboital pain and severe joint pains. During current epidemic various mucocuatneous manifestations have been seen among patients. Pigmentation was the most common cutaneous manifestation followed by maculopapular rash. Other features include apthous ulcer, urticarial wheals, petechaie and psoriasis vulgaris. These mucocutaneous features may help in differentiating various acute viral exanthems.